« Il est fascinant de voir comment se tisse une toile, se déploie ou se défriche un chemin de recherche. Je veux dire : collectivement. » - Aurore Turbiau; Vicky Gauthier; Isabelle Boiclair (Glad!)
The interview reproduced below took place on July the 1st, 2021, by videoconference, due to the French-Quebec conversation and the pandemic context.The conversation first focused on Isabelle Boisclair's career as a researcher. It seems to us that if we wish to study the “constellations” in this issue - of characters, authors, artists, titles - we must also trace the constellations constituted by gender studies research itself: in a way, those that allow the tracing itself to take place, the material and institutional basis of the reflections that have led us. It is therefore also a matter of recognizing the mixture of randomness, taste for knowledge, militancy and pleasure that little by little builds up our paths as researchers, the networks in which we are involved - or not -, the work that carries us forward and the way in which we re-imagine, in retrospect, this path.